Stretchable helical architecture inorganic-organic hetero thermoelectric generator. (December 2016) - Rojas, Jhonathan P.; Singh, Devendra; Conchouso, David; Arevalo, Arpys; Foulds, Ian G.; Hussain, Muhammad M.
Abstract: To achieve higher power output from a thermoelectric generator (TEG), one needs to maintain a larger temperature difference between hot and cold end. In that regard, a stretchable TEG can be interesting to adaptively control the temperature difference. Here we show, the development of simple yet versatile and highly stretchable thermoelectric generators (TEGs), by combining well-known inorganic thermoelectric materials Bismuth Telluride and Antimony Telluride (Bi2 Te3 and Sb2 Te3 ) with organic substrates (Off-Stoichiometry Thiol-Enes polymer platform – OSTE, polyimide or paper) and novel helical architecture (double-arm spiral/helix) to achieve over 100% stretchability. First, an OSTE-based TEG design demonstrates higher open circuit voltage generation at 100% strain than at rest, although it exhibits high internal resistance and a relatively complex fabrication process. The second, simpler TEG design, achieves a significant resistance reduction and two different structural substrates (PI and paper) are compared. The paper-based TEG generates 17 nW (ΔT=75 °C) at 60% strain, which represents more than twice the power generation while at rest (zero strain). On the other hand, polyimide produces more conductive TE films and higher power ( 35 nW at ΔT=75 °C) but due to its higher thermal conductivity, power does not increase at stretch. In conclusion, highly stretchable TEGs can lead to higher temperature gradients (thus higher power generation), given that thermal conductivity of the structural material is low enough. Furthermore, either horizontal or vertical displacement can be achieved with double-arm helical architecture, hence allowing to extend the device to any nearby and mobile heat sink for continuous, effectively higher power generation. Graphical abstract: Highlights: Stretchable TEGs, capable of temperature-gradient adjustment, are demonstrated. Higher power is observed at stretching if thermal conductivity of base material is low. Reducing legs' length helps to reduce internal resistance and increase performance.